2017
DOI: 10.1186/s13229-017-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing and proteomics approaches reveal novel deficits in the cortex of Mecp2-deficient mice, a model for Rett syndrome

Abstract: BackgroundRett syndrome (RTT) is an X-linked neurodevelopmental disorder caused by mutations in the transcriptional regulator MeCP2. Much of our understanding of MeCP2 function is derived from transcriptomic studies with the general assumption that alterations in the transcriptome correlate with proteomic changes. Advances in mass spectrometry-based proteomics have facilitated recent interest in the examination of global protein expression to better understand the biology between transcriptional and translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 153 publications
7
76
2
Order By: Relevance
“…In an attempt to identify region specific gene expression, studies were conducted on individual brain regions and cells isolated from these regions. These included the cortex (Kishi et al, ; Pacheco et al, ; Tudor, Akbarian, Chen, & Jaenisch, ; Urdinguio et al, ), visual cortex (Gabel et al, ; Renthal et al, ), the cerebellum (Ben‐Shachar et al, ; Gabel et al, ; Jordan, Li, Kwan, & Francke, ; Mellen, Ayata, & Heintz, ; Mellen, Ayata, Dewell, Kriaucionis, & Heintz, ; Sanfeliu, Hokamp, Gill, & Tropea, ; Urdinguio et al, ), whole brain (Guo et al, ; Kriaucionis et al, ; Nuber et al, ), the whole hippocampus (Baker et al, ; Tudor et al, ), and the amygdala (Samaco et al, ). Studies were also conducted on cell sources originating from distinct regions of the brain including forebrain (Tudor et al, ), hypothalamus (Chahrour et al, ; Chen et al, ), midbrain (Urdinguio et al, ), and striatum (Zhao, Goffin, Johnson, & Zhou, ), granule cells of the dentate gyrus hippocampal region (Smrt et al, ), embryonic cortical neurons (Bedogni et al, ; Vacca et al, ), and excitatory and inhibitory cortical neurons (Johnson et al, ).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an attempt to identify region specific gene expression, studies were conducted on individual brain regions and cells isolated from these regions. These included the cortex (Kishi et al, ; Pacheco et al, ; Tudor, Akbarian, Chen, & Jaenisch, ; Urdinguio et al, ), visual cortex (Gabel et al, ; Renthal et al, ), the cerebellum (Ben‐Shachar et al, ; Gabel et al, ; Jordan, Li, Kwan, & Francke, ; Mellen, Ayata, & Heintz, ; Mellen, Ayata, Dewell, Kriaucionis, & Heintz, ; Sanfeliu, Hokamp, Gill, & Tropea, ; Urdinguio et al, ), whole brain (Guo et al, ; Kriaucionis et al, ; Nuber et al, ), the whole hippocampus (Baker et al, ; Tudor et al, ), and the amygdala (Samaco et al, ). Studies were also conducted on cell sources originating from distinct regions of the brain including forebrain (Tudor et al, ), hypothalamus (Chahrour et al, ; Chen et al, ), midbrain (Urdinguio et al, ), and striatum (Zhao, Goffin, Johnson, & Zhou, ), granule cells of the dentate gyrus hippocampal region (Smrt et al, ), embryonic cortical neurons (Bedogni et al, ; Vacca et al, ), and excitatory and inhibitory cortical neurons (Johnson et al, ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The proteomic studies identified were conducted on three different Mecp2 mouse models: Mecp2 ‐null, Mecp2 308 , and Mecp2 Jae mice (Cortelazzo et al, ; Matarazzo & Ronnett, ; Pacheco et al, ). The ages of mice ranged from 2 weeks to 12‐months old.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, RTT-L-causing genes are directly involved in the MECP2-involved pathways of chromatin regulation (HDAC2, MEF2C, CREB1, GRIN1) and upregulation of glutamate and downregulation of dopamine and GABA pathways (CREB1, KCNA2, GRIN1, KCNB1, GRIN2A, GRIN2B, and KCNQ2) 42 . And while the RTT-L-causing genes do not play a role in the transcriptome profiling described by Lin et al, they share overlapping biological processes in many neuronal functions that have altered expression in RTT, such as synaptic transmission, neurotransmission, excitation of neurons, and development of neurons 43,44 . The involvement of many RTT-L-implicated genes in MECP2 function indicates that the replication of many of clinical features of RTT-L similar to that of classical or atypical RTT could be attributed to the disruption of one of MECP2's transcription regulatory activities.…”
Section: Discussionmentioning
confidence: 96%